Experts, reputation and umbrella Effects: Empirical evidence from wine prices - Dieter Pennerstorfer; Christoph R. Weiss; Andreas Huber (Johannes Kepler University of Linz, Department of Economics, 2019)
We investigate the relationship between external quality evaluation via experts, firm reputation and product prices and extend the existing empirical literature in three dimensions. First, we empirically account for endogenous reputation effects. An increase in quality has an immediate positive impact on product prices but also improves the reputation of a firm, which contributes to higher prices in the future. Secondly, we analyse umbrella effects of reputation: investments in product quality of the "top product" are particularly profitable as they also generate a "reputational dividend" for other products with lower quality. And finally, we investigate selection effects in expert evaluations. Experts typically evaluate a selection of products only and we find endogenous selection effects to be important for analysing product quality empirically.
Keywords: C33; L66; Q11; 330; experts evaluations; hedonic pricing; wine quality; endogenous reputation; sample selection; umbrella branding